KNOWLEDGE OF STANDARD PRECAUTIONS AND ASSOCIATED FACTORS AMONG NURSES AT HAI PHONG PEDIATRIC HOSPITAL IN 2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess nurses’ knowledge of standard precautions at Hai Phong Pediatric Hospital in 2026 and identify associated factors.Methods: A cross-sectional study was conducted among 242 nurses from January to May 2026. Data were collected using a structured self-administered questionnaire including 74 knowledge items. Adequate knowledge was defined as achieving ≥75% of the total score. Data were analyzed using descriptive statistics, Chi-square/Fisher’s exact tests, and multivariable logistic regression.Results: The mean knowledge score was 60.61 ± 6.48 (out of 74), with 77.7% of nurses having adequate knowledge. Higher scores were observed in respiratory hygiene, safe injection, and sharps injury prevention, while lower scores were found in general knowledge and personal protective equipment. Multivariable analysis showed that nurses trained according to Decision No. 3671/QD-BYT were more likely to have adequate knowledge (aOR = 5.67; 95% CI: 2.87–11.20; p < 0.001).Conclusion: Nurses’ knowledge of standard precautions was relatively good but gaps remained in key domains. Training based on Ministry of Health guidelines was independently associated with adequate knowledge. Strengthening regular training programs, especially in weaker areas, is recommended.
Keywords: standard precautions, knowledge, nurses, infection control